SnO2/TiO2 Thin Film n-n Heterostructures of Improved Sensitivity to NO2 - Piotr Nowak; Wojciech Maziarz; Artur Rydosz; Kazimierz Kowalski; Magdalena Ziąbka; Katarzyna Zakrzewska (Sensors, 2020)
Thin-film n-n nanoheterostructures of SnO2/TiO2, highly sensitive to NO2, were obtained in a two-step process: (i) magnetron sputtering, MS followed by (ii) Langmuir-Blodgett, L–B, technique. Thick (200 nm) SnO2 base layers were deposited by MS and subsequently overcoated with a thin and discontinuous TiO2 film by means of L–B. Rutile nanopowder spread over the ethanol/chloroform/water formed a suspension, which was used as a source in L–B method. The morphology, crystallographic and electronic properties of the prepared sensors were studied by scanning electron microscopy, SEM, X-ray diffraction, XRD in glancing incidence geometry, GID, X-ray photoemission spectroscopy, XPS, and uv-vis-nir spectrophotometry, respectively. It was found that amorphous SnO2 films responded to relatively low concentrations of NO2 of about 200 ppb. A change of more than two orders of magnitude in the electrical resistivity upon exposure to NO2 was further enhanced in SnO2/TiO2 n-n nanoheterostructures. The best sensor responses RNO2/R0 were obtained at the lowest operating temperatures of about 120 °C, which is typical for nanomaterials. Response (recovery) times to 400 ppb NO2 were determined as a function of the operating temperature and indicated a significant decrease from 62 (42) s at 123 °C to 12 (19) s at 385 °C A much smaller sensitivity to H2 was observed, which might be advantageous for selective detection of nitrogen oxides. The influence of humidity on the NO2 response was demonstrated to be significantly below 150 °C and systematically decreased upon increase in the operating temperature up to 400 °C.